(untitled) (Bangladesh Journal of Agricultural Research, 2012)
Bangladesh has immense prospect for exporting vegetables to the world market and it has also produced high quality exportable fresh vegetable. Although the share of export earning in vegetables increasing day by day but export is constrained by several issues. Thus the present study was undertaken to determine the value addition, cost and return of vegetables production and export at different levels and also suggest some policy implication for improving the present system. The study was based on both primary and secondary data. The sample included vegetables producer, suppliers, and exporters. Vegetable producers and suppliers were selected from Ulokhola of Kaligonj Upazila and exporters were selected from Dhaka city (Motijheel, Kakrail, Shantinagar, Khilgaon, and Sham Bazar).Appling conventional profitability analysis the study revealed that per hectare production cost for cowpea, snake gourd, and bitter gourd were estimated at Tk. 73838, Tk.72,029 and Tk.1,04,644 respectively and value addition for cowpea, snakegroud, and bitter gourd were calculated at Tk.86,162, Tk.1,52,611 and Tk.2,37,356 respectively by farmers. The average estimated marketing costs incurred by suppliers were Tk.2906 per ton. The value addition by suppliers were Tk.3094 per ton. The average estimated marketing cost incurred by different exporters for UK, Saudi Arabia, Kuwait, and Qatar were Tk.1,69,442, Tk.98,429, Tk.1,03,499, and Tk.85,324 per ton, respectively. The value addition by different exporters for UK, Saudi Arabia, Kuwait, and Qatar were Tk.55,778, Tk.16,661, Tk.16,902, and Tk. 23,754 per ton respectively. Among all the cost items, airfreight charge was the highest. It was revealed from the study that bitter gourd cultivation is more profitable and BCR is also highest (3.27) and UK market was more profitable for vegetables export. Bangladesh J. Agril. Res. 37(3): 377-388, September 2012 DOI: http://dx.doi.org/10.3329/bjar.v37i3.12081